Morbidity and Mortality in Rectal Surgery: A Study of 25 Cases in Casablanca - Hajri, Amal; Belbsir, Mohamed; Elwassi, Anas; Erguibi, Driss; Boufettal, Rachid; Rifki Jai, Saad; Chehab, Farid (European Scientific Journal, ESJ, 2025)
Rectal surgery is the only potentially curative treatment for many rectal pathologies, whether benign or malignant. However, postoperative complications can significantly impact the prognosis of patients. This retrospective study aimed to investigate morbidity and mortality among patients undergoing rectal cancer surgery over a two-year period at the Department of Digestive Cancer Surgery and Hepatic Transplantation of Ibn Rochd University Hospital (CHU) in Casablanca, Morocco. Among 62 patients, the average age was 61.98 ± 10.2 years (mean ± SD), with a female-to-male ratio of 1.5. Overall morbidity and mortality rates were 40.3% and 12%, respectively. Postoperative complications primarily included surgical site infections (40%) and urinary infections (20%), while long-term complications comprised incisional hernias (20%) and sexual problems (8%). The primary cause of mortality was intraoperative hemorrhage (8%) (Almatroudi, 2020). Factors influencing morbidity and mortality included age, BMI, comorbidities, type of intervention, and the benign or malignant nature of the pathology. Neoadjuvant chemotherapy was administered to 88% of patients and should be considered a key factor influencing outcomes, as it may contribute to better tumor control and reduce the extent of surgical resections required (Gado et al., 2014). The small sample size of this study may limit the statistical significance of the findings. Further research with a larger cohort is necessary to corroborate these results.